Performance analysis of IoT- Based cyanosis detection device in medical training - Azmi, Nur Fatihah; Septiadi, Nor Liyana; Delbressine, Frank (Wydawnictwo SIGMA-NOT, 2023)
Cyanosis is a blue coloration around the mouth and lips. Since cyanosis is a symptom of a potentially serious and life-threatening disease as heart failure, an early, fast, and accurate recognition of cyanosis coloration is crucial. Cyanosis recognition in a newborn baby is quite challenging as color is perceived subjectively among new medical trainees. Cyanosis color can be influenced by lighting conditions, colored objects around the baby, visual perception, and the eyes condition of the observer. Hence, this project aims to develop the IoT based cyanosis detection device for newborn assessment in medical training application that aims to detect and evaluate correct cyanosis color values. The proposed system is a combination of hardware and software development and has been integrated with IoT applications for data monitoring and analysis. The feedback from the user is gathered to get their expectations and design requirements. The next design solution is prototype construction which is based on the user’s preferences from the conducted market survey. For conclusion, the color error, comparison of color swatch between the actual and measured color, and the status of the data whether cyanosis or non-cyanosis was analyzed using the developed cyanosis device.